2011
DOI: 10.1111/j.1440-172x.2010.01905.x
|View full text |Cite
|
Sign up to set email alerts
|

Healthy lifestyle behaviour in university students and influential factors in eastern Turkey

Abstract: This research was carried out to determine the healthy lifestyle behaviour of university students receiving education in central Erzincan. The population of this descriptive and cross-sectional research included a total of 4506 students receiving education at Erzincan University in the city centre, and the sampling included 981 students selected by a simple random sampling method from these schools. Data were collected between April and May 2008 by using an identification form and the Health Promotion Life-Sty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
56
3
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 16 publications
19
56
3
14
Order By: Relevance
“…No statistical significant difference was found between gender and the mean total score for HPLP. This result is similar to those obtained in previous studies [15] [21].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…No statistical significant difference was found between gender and the mean total score for HPLP. This result is similar to those obtained in previous studies [15] [21].…”
Section: Discussionsupporting
confidence: 83%
“…Other potential explanation can be that students are loaded by heavy studying duties at university, and they need extra hours to study at home. Interestingly, other western studies reported similar results [15] [30].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations